1982
DOI: 10.2134/agronj1982.00021962007400050025x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Factors Influencing Soil Strength and Root Growth1

Abstract: Soil compaction is a major factor which influences root growth and crop yields. Studies were conducted to determine the influence of different factors on mechanical impedance and to determine the influence of mechanical impedance and other soil factors on root growth. Regression models for dependent variables, soil strength and root growth, vs. the independent variables, soil type, soil depth, clay content, bulk density, voids, and water content were computed using the maximum R2 improvement by stepwise regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
8

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 3 publications
(4 reference statements)
3
56
0
8
Order By: Relevance
“…Further possible explanations are the generally increasing water contents with depth at field condition (for Bt-2) or with increased water content caused by exudates (REW, Bt-1). Gerard et al (1982) computed regression models (stepwise) for both, root growth and soil strength, as dependent variables, using soil type, soil depth, clay content, bulk density, voids, and water content as independent variables. The considered soil types were a sandy loam and a clay loam.…”
Section: R Ew Rewmentioning
confidence: 99%
“…Further possible explanations are the generally increasing water contents with depth at field condition (for Bt-2) or with increased water content caused by exudates (REW, Bt-1). Gerard et al (1982) computed regression models (stepwise) for both, root growth and soil strength, as dependent variables, using soil type, soil depth, clay content, bulk density, voids, and water content as independent variables. The considered soil types were a sandy loam and a clay loam.…”
Section: R Ew Rewmentioning
confidence: 99%
“…Em um Podzólico Vermelho-Amarelo franco-arenoso, Silva et al (2000) não observaram redução da produtividade do milho após a compactação pelo pisoteio animal, nos sistemas de preparo convencional e plantio direto, apesar de haver concentração das raízes na camada superficial do solo no plantio direto. Gerard et al (1982) afirmaram que a resistência do solo à penetração, considerada crítica ao crescimento das raízes, diminui com o aumento no teor de argila do solo. Portanto, em solos mais argilosos, o aumento da densidade do solo e da resistência do solo à penetração pode ser mais restritivo às raízes do que em solos arenosos.…”
Section: Introductionunclassified
“…The high penetrometer readings of the Andigama series was due to the inherent nature of the soil profile. As reported by Vidhana Arachchi (1996) the high amount of clay particles accumulating in the sub-horizon, cemented with gravel particles formed a hard layer in the Andigama series of which bulk density was greater than 1.6 g/cm\ Gerard et al, (1982) also reported that soil strength in a Miles fine sandy loam, Udic Paleustalf, and in an abilene clay loam, Pachic Argiustoll, were influenced by bulk density, voids, and clay content in their soil profiles. Results also showed that soil resistance increased beyond the 100 cm depth in both soil profiles.…”
Section: Penetrometer Resistancementioning
confidence: 58%